The Effectiveness of Self-Management Approaches on Improving Self-Efficacy and Quality of Life in Stroke Patients Undergoing Rehabilitation Programs: A Systematic Review - Eppy Setyowati; Mardliyah Mardliyah; Sumiatin Sumiatin; Winarti Winarti (Indonesian Journal of Global Health Research, 2026)
Stroke is a major global health problem and one of the leading causes of long-term disability and death worldwide. Post-stroke patients often experience decreased physical function and independence, while adherence to rehabilitation programs remains suboptimal due to low motivation, insufficient knowledge, and limited family support. The self-management approach has been introduced to encourage patients' active participation in their recovery process by improving self-efficacy and overall quality of life This study aims to evaluate the effectiveness of the self-management approach in improving self-efficacy and quality of life among post-stroke patients, and to critically appraise the quality of existing scientific evidence. This study applied a systematic review design following the PRISMA 2020 guidelines. Literature searches were conducted in PubMed, Scopus, Web of Science, Google Scholar, and Registers for studies published between 2020 and 2025. Of the 1,383 articles identified, 10 studies met the inclusion criteria and were analyzed.  All ten studies consistently demonstrated that self-management interventions effectively improved self-efficacy , adherence to rehabilitation, and quality of life in post-stroke patients. The interventions also promoted independence in daily living activities ( Activities of Daily Living/ADL ) and strengthened patients' confidence and motivation in managing their health. Additionally, family involvement and healthcare support were identified as key factors contributing to the success of self-management programs. The self-management approach is proven to be an effective strategy for enhancing self-efficacy and quality of life among stroke survivors. It empowers patients to actively engage in their physical, psychological, and social recovery. Therefore, self-management programs should be integrated into post-stroke rehabilitation as a sustainable and patient-centered intervention model in both clinical and community settings.